Formulation And Evaluation Of Black Glutinous Rice Clay Mask (Oryza sativa L. Var Glutinosa) Using Bentonite And Kaolin Variations - Fiskia, Ermalyanti; Nur, Amran; Cindhany Darmaria Faridha Utami Mala (Pharmacon: Jurnal Farmasi Indonesia, 2024)
Black glutinous rice is a staple cuisine consumed frequently by Indonesians. Black glutinous rice's high anthocyanin content can stimulate collagen production. This study seeks to determine the effects of the kaolin and bentonite combination on different concentrations as a clay mask and obtain the optimal composition formula. Optimizing the clay mask formula using the factorial design procedure. The evaluation of a formula includes organoleptic, homogeneity, pH, irritation, and drying time tests. The research findings indicated that all preparations satisfied the evaluation criteria before the pH test. The results showed that kaolin can elevate the pH level, while bentonite can lower the pH. Preparations F1 and F2 satisfy the requirements, whereas F3 fails to fulfil the standards following the pH test. F1 (5 % bentonite and 15 % kaolin) and F2 (3 % bentonite and 25 % kaolin) were optimal clay mask formulas for black glutinous rice.